IMPLEMENTASI DAN PEMAHAMAN DOKUMEN KREDIT SALAH SATU BANK DI SURABAYA - Veronica Mechy Luklu’ul Firdaus; Siti Ning Farida (CV. ALIM'SPUBLISHING, 2024)
PT Bank Negara Indonesia (Persero) Tbk or commonly abbreviated as BNI, is an Indonesian state-owned enterprise that provides various financial services. one part of finance is kredit administration, kredit administration is the process of managing and supervising the provision of kredit and monitoring payments from borrowers. in general, kredit administration includes the kredit assessment process, kredit granting decision-making, and risk management during the kredit period. The Kampus Merdeka Internship Regular Program is an activity carried out by the government from the Ministry of Education and Culture to provide space for students to gain experience in understanding the professional world and creating a professional workforce so that students are given the opportunity to help manage the Kredit administration process at.